PENGARUH PERSEPSI KEGUNAAN DAN PERSEPSI KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE SHOP TOKOPEDIA - Agtovia Frimayasa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Technological developments are increasing rapidly, encouraging industry players to innovate in the field of technology, one of which is online shopping transactions, namely Online shopping. There are many online shops present, one of which is Tokopedia. Tokopedia is still one of the online shops that are popular with consumers. This is inseparable from the role of consumers in purchasing decisions which are quite high. Purchasing decisions are one of the most important factors in marketing management because purchasing decisions are the basis for the birth of a purchase. And sampling by sampling technique, namely accidental sampling based on the formula proportion of sampling. Data collection includes observation, distribution of questionnaires and literature study. This study aimed to determine the effect of Perceived Usefulness and Perceived Convenience on the Buying Decision of the Tokopedia Online Shop. The research approach used in this study is a quantitative approach with a total sample of 100 respondents. Perceived usefulness has a significant and partially positive effect on purchasing decisions at Tokopedia. Perceived convenience has a significant and partially positive effect on purchasing decisions at Tokopedia. Adjusted R Square calculation results show that 46.9% of Purchasing decisions can be influenced by Perceived usefulness and Perceived Convenience.